Pelaksanaan Program Pembinaan Kemandirian Anak Sebagai Usaha Penanggulangan Kejahatan pada Lembaga Pembinaan Khusus Anak Kelas II Batam - Stevany Stevany; Dudi Badruzaman (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
Corrections are activities that provide guidance for Correctional Inmates (WBP) which are carried out by correctional institutions in accordance with the mandate of Law Number 22 of 2022. Carrying out prison guidance also contributes to the reintegration of Inmates into society. The goal is for inmates to become better people when they are free. The aim of this research is to see how the program for fostering children's independence is used to prevent crime, especially at the Batam Class II Special Children's Penitentiary. This research was conducted there using a normative juridical approach. To do this, literature studies, observations and interviews were carried out. Data sources include structured interviews, the 1945 Constitution of the Republic of Indonesia, and laws relating to the development of child prisoners. The research results show that Law Number 22 of 2022 and other laws that complement it can function as a legal basis for fostering the independence of child prisoners. This will enable the implementation of fostering independence for child prisoners to be clearer so that the determination process can run as it should.